Analisis Bayangan Dalam Macbeth Karya William Shakespeare - Tuti Handayani; Syahrul Ramadhan; Siti Armelia Hamidah (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Macbeth was one of William Shakespeare's famous plays that used many shadows to beckon events to come in this story. In Macbeth's stories shadows are used to create tensions and raise questions about agency and moral responsibility in the drama. This study aims to analyze and identify the use of additives in the text and connect it to the development of themes and characters in Macbeth's story. In addition, the researchers also used interpretation and evaluation. After evaluating